Multiple Mathematical Representations in Ethnomathematics-Based Realistic Mathematics Education: A Systematic Literature Review - Setianingsih, Rini; Prayogo, Mochammad Reval Ardhi Yudi; Putri, Alvinna Mei Yunia (International Journal of Review in Mathematics Education, 2026)
Research on ethnomathematics-based Realistic Mathematics Education (Ethno-RME) has grown significantly in recent years, particularly in relation to its potential to support meaningful and culturally grounded mathematics learning. However, there remains limited systematic understanding of how multiple mathematical representations function within this framework, especially in facilitating representational transitions and conceptual understanding. This study aims to synthesize and analyze research on Multiple Mathematical Representations (MMR) within Ethno-RME through a Systematic Literature Review. The review identifies the types of representations employed, their roles in the mathematization process, and their contributions to mathematics learning outcomes. A systematic procedure consisting of planning, conducting, and reporting stages was implemented. Articles were retrieved from the Scopus database using the Publish or Perish tool and selected based on predefined inclusion and exclusion criteria, resulting in ten eligible peer-reviewed studies published between 2016 and 2025. The findings indicate that Ethno-RME consistently promotes the development and coordination of multiple representations, including visual, symbolic, verbal, contextual, and technological forms. Cultural contexts function as meaningful entry points that initiate representational construction and facilitate the transition from informal situational models to formal mathematical abstraction through progressive mathematization. The synthesis further reveals that representational coordination enhances conceptual understanding, problem-solving ability, numeracy skills, creativity, and higher-order thinking. Moreover, mathematical representation emerges as a bridging role linking contextual experience and formal reasoning. Overall, this review establishes that multiple mathematical representations constitute a foundational mechanism within ethnomathematics-based RME, supporting meaningful, culturally grounded, and conceptually robust mathematics learning.